Evaluation of the use of Cocos nucifera as antimalarial remedy in Malaysian folk medicine - Al-Adhroey, A.H.; Nor, Z.M.; Al-Mekhlafi, H.M.; Amran, A.A.; Mahmud, R. (2011)
Ethnopharmacological relevance: White flesh extract of Cocos nucifera (coconut) was studied to ascertain the ethnopharmacological standing of its antimalarial usage in Malaysian folk medicine. Materials and methods: The crude methanol extract was investigated for phytochemical constituents and acute oral toxicity. Antimalarial activity of different extract doses of 50, 100, 200 and 400 mg/kg were investigated in vivo against Plasmodium berghei (NK65) infections in mice during early, established and residual infections. Chloroquine (20 mg/kg) and pyrimethamine (1.2 mg/kg) were used as reference drugs. Results: The results revealed that the extract contained some phytochemical constituents and is toxicologically safe by oral administration. The extract significantly reduced the parasitaemia by the 200 and 400 mg/kg doses in the all three in vivo assessment assays. However, the extract did not significantly increase the survival time of the infected mice. Conclusions: The observed pharmacological activities suggest that the Malaysian folkloric medicinal application of Cocos nucifera has a pharmacological basis. (C) 2011 Elsevier Ireland Ltd. All rights reserved.